Depression and Self-Efficacy Among Iranian Children During the Prevalence of COVID-19 Disease - Zakeri, Mohammad Ali; Dakkalirad, Abdollah; Saedi, Fahimeh; Shahnavazi, Allahyar; Kordi, Mehri; Ahmadipour, Maryam; Dehghan, Mahlagha (Frontiers in Pediatrics, 2022)
The COVID-19 outbreak has quickly endangered the physical and mental health of people in the community, particularly vulnerable people such as children. This study was carried out to investigate the depression and self-efficacy of Iranian children during the COVID-19 outbreak. This cross-sectional research was conducted on 321 children in southeast Iran. A social media-based online questionnaire was used to collect data. The information was gathered using demographic and COVID-related items, the Children's Depression Inventory (CDI), and Self-Efficacy Questionnaire for Children (SEQ-C). No significant correlation was observed between depression and self-efficacy of children (P = 0.23). However, in subscale of CDI, negative mood, ineffectiveness and negative self-esteem had a significant relationship with self-efficacy (<0.001). Depression had a significant association with income of family (p = 0.017), being at risk of coronavirus infection (p = 0.036), effectiveness of preventive measures (p = 0.015) and how information about the coronavirus disease were obtained (p = 0.018). The rate of depression in Iranian children in this study was high, according to the results, and it is necessary to take the necessary measures and treatment plans to reduce the rate of depression in children. Further research is needed to assess and prevent childhood depression.